(untitled) (Third Sector Social Economic Review, 2019)
In recent years, entrepreneurship activities have become an important type of economic activity for the development of countries. Lack of infrastructure in many developing countries Turkey and such as Turkey financial inefficiencies and bureaucratic obstacles, poses significant barriers to entrepreneurs in entrepreneurship activities. The only way to overcome such obstacles is to make sure that the problem is correctly identified and that various studies and arrangements are made in order to produce effective solutions to the problem.In this study, prepared to examine the development of global entrepreneurship in Turkey with the help of Turkey’s global Entrepreneurial and Development Index (GEDI), although Turkish entrepreneurs do not face significant problems with the domestic market dynamics and market pitch, economic growth, risk management and product development, research development, production of new technologies and the provision of funding A number of problems have been achieved.